The special corporate regime in Colombia (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
A theoretical study and practical analysis are conducted on a type of company that is established in Colombia by one or more natural or legal persons, with the purpose of carrying out activities for the benefit of their members, third parties, or the community in general. These are referred to as "non-profit entities" (ESAL). The document also emphasizes donations, tax incentives, and the Special Tax Regime (RTE), terms inherent to this type of company with a special tax regime. It is clearly explained how they have evolved and the significance they have had in the country. The document shows how ESALs prove to be an excellent option for development and support for government public policies. After presenting various general interest criteria related to taxes and exemptions, clarification is made regarding these types of entities in the capital district of Bogotá, where they are evidenced in considerable numbers. They are analyzed using a statistical measurement instrument to determine their status, quantity, and types of companies under this modality. Finally, an example of an ESAL is presented, demonstrating its involvement in society, including sectors such as academia through strategic alliances.
Keywords: incentives; donations; special tax regime